A Constrained Analysis of the 40Ca(18O,18F)40K Direct Charge Exchange Reaction Mechanism at 275 MeV - Cavallaro, Manuela; Bellone, Jessica I.; Calabrese, Salvatore; Agodi, Clementina; Burrello, Stefano; Cappuzzello, Francesco; Carbone, Diana; Colonna, Maria; Deshmukh, N.; Lenske, H.; Spatafora, A.; Acosta, L.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
The 40Ca(18O,18F)40K single charge exchange (SCE) reaction is explored at 275 MeV incident energy and analyzed consistently with elastic and inelastic scattering data collected in the same experimental conditions. Fully quantum mechanical SCE calculations of the direct mechanism are performed including microscopic nuclear structure inputs and adopting either a bare optical potential or a coupled channel equivalent polarization potential constrained by elastic and inelastic data. The direct SCE mechanism describes magnitude and shape of the angular distributions rather well, thus suggesting the suppression of sequential multi-nucleon transfer processes.